EFEKTIVITAS PROGRAM PENCEGAHAN STUNTING MELALUI APLIKASI ELSIMIL PADA BALAI PENYULUH KELUARGA BERENCANA KECAMATAN PASEH KABUPATEN SUMEDANG - Devindra Rizqiana (JRPA - Journal of Regional Public Administration, 2026)
Stunting is a chronic nutritional problem that has a long-term impact on children's physical and cognitive growth. To overcome this problem, the government through BKKBN developed the Elsimil Application (Electronic Ready for Marriage and Pregnancy) as one of the stunting prevention strategies implemented in various regions, including Paseh District, Sumedang Regency. This study aims to analyze the effectiveness of stunting prevention programs through the Elsimil Application at the Balai Penyuluh KB of Paseh District, Sumedang Regency using the theoretical model from Budiani in Indriati (2019: 152-153). The research uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study show that the implementation of the program still faces various obstacles, such as a complex application system that often experiences disruptions, a lack of maximum socialization to officers and targets, and weak monitoring in mentoring reporting. Efforts made to overcome these obstacles include increasing understanding through training, improving application systems, and optimizing the role of the Family Assistance Team. This study concludes that despite the obstacles in implementation, the Elsimil Application has significant potential in reducing stunting rates if supported by a stable system, equitable socialization, and consistent supervision.